Multidisciplinary guidelines on hospitalization and post-discharge recommendations (Research, Society and Development, 2024)
Objectives: to identify gaps in multidisciplinary guidance that caregivers and patients present during the hospitalization process and to propose educational material with multidisciplinary guidance aimed at hospital care, including considering the transition to discharge. Method: Descriptive and qualitative research. The study site was the medical clinic wards of a federal teaching hospital in Rio de Janeiro. Nine companions and two elderly patients responsible for their own care during hospitalization and at home participated in the study. The data collection technique was semi-structured interviews. Results: The dialogue allowed access to the guidance provided by the multidisciplinary team that the participants would like to know. Some were surprised, took a long time to respond and when they did respond, they did not know what type of guidance would be essential for better monitoring of the elderly person during hospitalization and in preparation for discharge. They were also unaware of the role and interaction of the professions in the multidisciplinary team. During the hospitalization of the elderly person, the care provided by caregivers often results from previous care experiences or observation of other patients who are in the ward. Access to the topic made it possible to propose educational material in the form of a folder. Conclusion: The results showed that communication between caregivers, elderly individuals and the health team during the hospitalization period in the sector is structured according to the biomedical model. The educational material developed can be considered an important strategy for mediation between the multidisciplinary team, companions and elderly individuals in the hospital. Furthermore, it contributes to expanding the scope of multidisciplinary actions.